ANALYSIS OF DEVELOPMENT OF THE PROBLEM OF DEVIANT BEHAVIOR OF ADOLESCENTS IN SCIENTIFIC LITERATURE (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem concerning the practice of investigating deviant behaviour of teens in psychological and pedagogical literature. The problem of deviant behaviour is actual today for all the participants in educational process: pupils, pedagogues, parents.